Audio-Visual Hallucinations in a Patient Poststem Cell Transplant - Kapoor, Astha Koolwal (Indian J Palliat Care, 2019)
Tramadol is the most common weak opioid used today. It has unique pharmacology and is notorious for numerous side effects as well as drug interactions. Patients undergoing stem cell transplant are susceptible to polypharmacy as a result of the generous use of antibiotics and symptom management drugs. Here, we describe a case where concurrent use of tramadol and fluconazole can cause hallucinations as a result of drug interaction.